Inclusive Innovation Policies as a Way towards Inclusive Growth in CEE Countries - Dorota MURZYN (Communications of International Proceedings, 2020)
The aim of the paper is to achieve two objectives. Firstly, it examines the level of inclusive growth in CEE countries; secondly, it explores the role of inclusive innovation policies in fostering inclusive growth. From a methodological point of view, the author uses a descriptive analysis and statistical analysis. This paper contributes to theoretical debates on inclusive growth processes in CEE countries, but it also provides policy insights on the relationship between inclusive innovation policy and inclusive growth. CEE countries differ in terms of the level of inclusive growth, with the highest being observed in Slovenia and the lowest in Romania. We can observe an increase in the level of development in each country (in the years 2008-2018), with some developing faster than others - the highest increase occurred for Latvia and the smallest for Slovakia and Hungary. There is a need for inclusive innovation policies in CEE countries, and a wide range of such policy approaches can foster inclusive growth. To achieve such growth, it is necessary to remove barriers for disadvantaged groups, laggard firms and regions to enable all segments of society to participate in and benefit from innovation. The success of inclusive innovation policies relies on the stronger involvement of target groups and often requires strong capacity-building efforts and adequate financial support.
Keywords: Inclusive innovation policy; inclusive growth; CEE countries.